The Implementation of Regional Governmental Bureaucracy Reformation of Bandung City - Andrian; Muradi; Mudiyati Rahmatunnisa; Dede Sri Kartini (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
This study analyzes the implementation of regional government bureaucratic reform in the city of Bandung in 2015. This research was based on bureaucratic reform in the city of Bandung which has received a very good predicate from the Ministry of State Apparatus Empowerment and Bureaucratic Reform. This is because the local government of Bandung City has a strong mission to fix the bureaucracy in the region. In addition, theoretically the implementation of bureaucratic reform requires political support between the executive and legislature in making regulations or policies. This study explored bureaucratic reform which implies the role of the executive and legislature. This study was a qualitative approach with a case study method. The findings in this study were: (1) the success of the City of Bandung in obtaining a very satisfactory value from the Ministry of Administrative Reform and Bureaucratic Reform was due to the existence of political support both from the executive and legislative branches; (2) the executive and the legislature collaborated together to discuss and design governance, especially in the implementation of Bandung bureaucratic reform; and (3) the discussions carried out by the Executive and Legislature obtained a policy that led to an agreement and placed the discussion in the interests of the people of Bandung City, so that the implementation of Bandung City bureaucratic reform could be achieved properly.